Transcranial Doppler goal-directed therapy after cardiac arrest (GOODYEAR): a feasibility study - Juliette Meunier; Nicolas Engrand; Patrick Saulnier; Nicolas Deye; Mickaël Landais; Alain Cariou; Christophe Guitton; Nicolas Chudeau (Resuscitation Plus, 2025)
Aim: Hypoxic Ischemic Brain Injury is a major cause of death after cardiac arrest. Identifying optimal mean arterial pressure (MAP) targets to restore brain oxygen delivery remains challenging. This study assessed the feasibility of using transcranial Doppler to guide individualised MAP management in post-cardiac arrest patients. Methods: In this single-centre prospective feasibility study, post-cardiac arrest patients were enrolled after intensive care unit admission. After induction of targeted temperature management (TTM) and control of systemic secondary brain insults determinants, cerebral hypoperfusion was screened using transcranial Doppler. A MAP challenge was performed in patients with abnormal transcranial Doppler findings to assess cerebral vascular responsiveness to increased MAP. Jugular bulb oximetry was concurrently used to evaluate cerebral oxygenation. Results: A total of 172 patients were screened, and 20 (11.6%) were assessable using transcranial Doppler. After optimisation of cerebral blood flow determinants, 3 patients (15%) showed signs of cerebral hypoperfusion based on transcranial Doppler measurements. A MAP challenge was performed in two of these patients, without normalisation of transcranial Doppler values and with an estimated increase in intracranial pressure. No significant association was found between transcranial Doppler findings and either cerebral oxygenation parameters or neurological outcome. Baseline SjvO2 levels were paradoxically higher in non-survivors. Conclusions: Implementing an individualised MAP management strategy guided by transcranial Doppler was challenging, with few patients eligible for evaluation. Still, transcranial Doppler identified a small group with persistent cerebral hypoperfusion despite optimised cerebral blood flow parameters. The study underscored technical and physiological limitations of this approach, which should inform the design and relevance of a larger trial to assess its clinical value.Trial registration: https://www.clinicaltrials.gov NCT04000334.